The Influence of Tiktok Content Marketing, Promotion and Online Customer Review on Shopee Marketplace Towards Online Impulsive Buying (A Study on Bare n Bliss Shopee Consumers in Surabaya) - Choirunisa, Desnita Mazaya; Azizah, Nurul (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The development of digital technology has driven major changes in people's behavior in doing business, including in online shopping activities and also business marketing that has shifted to digital. The phenomenon of online purchases in society encourages online impulse purchases which are of particular concern. Bare n bliss is a beauty product that maximizes its product marketing digitally. Its products are actively promoted on tiktok social media, and bare n bliss is also present in the shopee marketplace to transact and maximize promotion and provide information. This study aims to analyze the influence of tiktok content marketing, promotions, and online customer reviews on shopee marketplace towards online impulsive buying in shopee consumers of Bare n Bliss products in Surabaya. The research method used is quantitative associative with sampling using purposive sampling which amounted to 110 respondents by distributing google forms to bare n bliss shopee consumers who are TikTok and Shopee application users that live in Surabaya. The data analysis technique used SPSS 27 software. The results showed that both partially and simultaneously, Tiktok content marketing, Promotion, and Online customer review had a positive and significant effect on Online impulsive buying.